HUBUNGAN KUANTITATIF ANTARA STRUKTUR DAN TOKSISITAS SENYAWA KLOROFENOL - Emdeniz - (Universitas Andalas, 2011)
Vol 5 No 1ABSTRACT Quantitative Structure-Activity Relationship (QSAR) for the toxicity of chlorophenols (CPs) from mono to pentachlorine substituted compounds has been done. The structural parameters are obtained from geometry structure optimization by computational chemistry using ab initio methods and the experimental data of acute toxicity (-log EC50 ) of chlorophenols to Daphnia magna were taken from the literature. The best QSAR model obtained by multilinier regression analysis, using the systematic approach for variable selection and the result showed that QSAR equations i.e: -log EC50 pre = -99.545 – 83.402 rOH + 145.879 rCO – 0.053 qO + 26.198 qH + 0.568 EH – 2.599 EL – 0.067 HE – 0.134 Rm + 0.133 μ (n = 18, R = 0.971, R2 = 0.943, SD = 0.447794, Fcal/Ftab = 3.956) Keywords: Chlorophenol, QSAR, toxicity